"If You Compete with us, We Shan'T Marry You" The (Mary Paley and) Alfred Marshall Lecture. Issue 6 (19th October 2021) - Pande, Rohini; Roy, Helena
Abstract: Alfred Marshall and Mary Paley Marshall are often described as the first academic economist couple. Both studied at the University of Cambridge, where Paley became one of the first women to take the Tripos exam and the first female lecturer in economics, with Marshall's encouragement. But in later life, Marshall opposed granting Cambridge degrees to women and their participation in academic economics. This paper recounts Alfred Marshall's use of gender norms, born out of a separate spheres ideology, to promote and ingrain women's exclusion in academic economics and beyond. We demonstrate the persistence of this ideology and resultant norms, drawing parallels between gendered inequities in labor market outcomes for Cambridge graduates in the UK post-Industrial Revolution and those apparent in cross-country data today. We argue that the persistence of the norms produced by separate spheres ideologies is likely to reflect, at least in part, the rents associated with preferential access to better paid, high-skilled labor market opportunities. In doing so, we ask who benefits from gender norms, who enforces them, and suggest relevant policy work and areas for future research.